Decision Support System Determines The Best Customers for Giving Rewards Using Weighted Product Method - Suwandi, Suwandi; Magdalena, Lena; Hidayat, Ade Rahmat; Dewi, Wiwiek Nurkomala; Kartika, Ika (Proceeding International Conference on Religion, Science and Education, 2025)
Giving rewards to the best customers is one strategy that can increase customer loyalty and satisfaction. The problem is that determining which customers are mostworthy of receiving rewards is often a challenge because it requires considering various criteria, such as number of purchases, frequency of visits, and length of membership. The object of this research is PT Citra Kreasi Makmur (CKM) Cirebon, which is one of the leading companies in Indonesia which has distribution rights for the best products and brands from all over the world, such as Philips Home Appliances and others. This research aims to develop a decision support system (DSS) that can help companies select the best customers for giving rewards using the Weighted Product (WP) method.The WP method was chosen because of its ability to carry out calculations based on the weight of each predetermined criterion. The selection process begins by collecting customer data and determining the weight for each criterion. After that, calculations are carried out using the WP method to produce the final value for each customer. The customer with the highest score is considered the best customer who is entitled to a reward. The results of this research can help companies make more objective and precise decisions in giving rewards, as well as increase customer loyalty. Apart from that, this system can also be developed further by adding other relevant criteria according to the company's needs.